"Awa ndi macheza aamai (This is women's play)": Examining Pleasure in Urban Malawian Women's Social Spaces. (14th December 2022) - Mtenje, Asante Lucy
Abstract: Women's social groups and gatherings in Malawi, whether physical or virtual, are often dismissed as something not to be taken seriously, as they are imagined to be places where nothing useful but chitchat and gossip will emerge. Nevertheless, these spaces, as sites of leisure where women can engage in macheza (play), continue to play an important role in how urban women variously experience pleasure. Mtenje considers social media groups for women and bridal showers not only as spaces where women are free from male interference, which, in itself, invokes pleasure, but also as spaces where patriarchal norms can be and often are reinforced.